Quantitative morphology of bedrock fault surfaces and identification of paleo-earthquakes - He, H.; Wei, Z.; Densmore, A.L. (Tectonophysics, 2016)
The quantitative analysis of morphologic characteristics of bedrock fault surfaces may be a useful approach to study faulting history and identify paleo-earthquakes. It is an effective complement to trenching techniques, especially to identify paleo-earthquakes in a bedrock area where trenching technique cannot be applied. In this paper, we calculate the 2D fractal dimension of three bedrock fault surfaces on the Huoshan piedmont fault in the Shanxi Graben, China using the isotropic empirical variogram. We show that the fractal dimension varies systematically with height above the base of the fault surface exposures, indicating a segmentation of the fault surface morphology. We interpret this segmentation as being due to different exposure duration of parallel fault surface bands, caused by periodical earthquakes, and discontinuous weathering. We take the average of fractal dimensions of each band as a characteristic value to describe its surface morphology, which can be used to estimate the exposure duration of the fault surface band and then the occurrence time of the earthquake that exposed the band. Combined with previous trenching results, we fit an empirical relationship between the exposure duration and the morphological characteristic value on the fault: D = 0.049 T + 2.246. The average width of those fault surface bands can also be regarded as an approximate vertical coseismic displacement of characteristic earthquake similar to the Hongdong M8 earthquake of 1303. Based on the segmentation of quantitative morphology of the three fault surfaces on the Huoshan piedmont fault, we identify three earthquake events. The coseismic vertical displacement of the characteristic earthquake on the Huoshan piedmont fault is estimated to be 3–4 m, the average width of these fault surface bands. Gaps with a width of 0.1–0.3 m between two adjacent bands, in which the fractal value increases gradually with fault surface height, are inferred to be caused by weathering between two earthquakes or interseismic slip on the fault.
EPrint Processing Status: Full text deposited in DRO